2004
DOI: 10.1071/zo04020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the enigmatic 'phascolosoricine' marsupials of New Guinea

Abstract: Previous analyses of DNA sequences for mitochondrial cytochrome-b and 12S rRNA, along with the nuclear protamine P1 genes, suggested that the New Guinean dasyurid genera Phascolosorex and Neophascogale (phascolosoricines) form the sister groups of quolls (Dasyurus) and Tasmanian devils (Sarcophilus). This runs counter to a common perception that phascolosoricines are anatomically primitive and only distantly related to other dasyurids. We report the DNA sequences of two additional mitochondrial loci (tRNAVal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Within the latter genus, the northern quoll ( Dasyurus hallucatus ) is clearly divergent from all others and Dasyurus maculatus is sister to a clade containing Dasyurus viverrinus , Dasyurus albopunctatus , Dasyurus geoffroii , and Dasyurus spartacus – as also suggested by Krajewski et al . (). Our expanded data set indicates with 100% bootstrap support that Dasyurus albopunctatus is sister to the other species in this group and that Dasyurus viverrinus is sister to Dasyurus geoffroii plus Dasyurus spartacus .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within the latter genus, the northern quoll ( Dasyurus hallucatus ) is clearly divergent from all others and Dasyurus maculatus is sister to a clade containing Dasyurus viverrinus , Dasyurus albopunctatus , Dasyurus geoffroii , and Dasyurus spartacus – as also suggested by Krajewski et al . (). Our expanded data set indicates with 100% bootstrap support that Dasyurus albopunctatus is sister to the other species in this group and that Dasyurus viverrinus is sister to Dasyurus geoffroii plus Dasyurus spartacus .…”
Section: Discussionmentioning
confidence: 97%
“…Krajewski et al . (, , ) and Westerman, Young & Krajewski () subsequently explored genus‐level affinities within Dasyuridae via extended mitochondrial ( cytb , 12S rRNA , tRNA valine + 16S rRNA ) and nuclear [ ProtP1 , interphotoreceptor binding protein exon 1 ( IBRP ), and beta‐fibrinogen intron 7 ( bfib7 )] gene sequences. Their results variously confirmed the monophyly of the dasyurin genus Pseudantechinus (including Pseudantechinus bilarni ), the sister placement of Neophascogale + Phascolosorex (‘Phascolosoricinae’ sensu Archer, , ) and Dasyurus + Sarcophilus , as well as the close relationship between Dasycercus and Dasyuroides .…”
Section: Introductionmentioning
confidence: 99%
“…Similar factors cannot be ruled out in the case of the early divergence between New Guinean Peltops and mostly Australian-centred Strepera plus Cracticus lineage (17-28 Ma). That case could be interpreted to support the hypothesis that rainforest-inhabiting lineages were able to persist in isolation on the proto-New Guinean islands prior to the formation of the current New Guinean landmass 2-5 Ma (Joseph et al, 2001;Krajewski et al, 2004;Westerman et al, 2006;Roelants et al, 2007;Malekian et al, 2010;Macqueen et al, 2010;JØnsson et al, 2011;Toon et al, 2012).…”
Section: Changes In Sea-level: Interchange Between New Guinea and Ausmentioning
confidence: 63%
“…Recent attempts using time-calibrated phylogenies have supported the hypothesis that increasing aridity from 25 Ma allowed the diversification of arid-adapted lineages in Australia (e.g. Crisp et al, 2004;Meredith et al, 2008;Fujita et al, 2010;Pepper et al, 2011;Toon et al, 2012), and that the proto-New Guinean islands supported biota prior to the formation of the New Guinean landmass (Joseph et al, 2001Krajewski et al, 2004;Westerman et al, 2006;Roelants et al, 2007;Malekian et al, 2010;Macqueen et al, 2010;Jønsson et al, 2011;Toon et al, 2012). However, there are still too few studies incorporating multilocus datasets and complete sampling of extant taxa and key geographic regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This accords with their current classification as C. h. superciliosa and suggests they maintained male-mediated gene flow during the LGM across then-exposed savannah woodlands and grasslands (Nix and Kalma 1972;Williams et al 2009). Grey shrike-thrush currently inhabit savannah areas within PNG and relatively shallow divergence across Torres Strait has been repeatedly observed in savannahadapted species (Keighley et al 2019;Murphy et al 2007;Toon et al 2017;Williams et al 2008;Wüster et al 2005) compared with deeper divergence observed in mesic closed forest-adapted species (Joseph et al 2001;Kearns et al 2011;Krajewski et al 2004;Macqueen et al 2011Macqueen et al , 2010Norman et al 2007;Rawlings and Donnellan 2003;Zwiers et al 2008). A mitochondrial lineage unique to the Trans-Fly was estimated to have diverged from mainland Australian and east PNG lineages 0.38-0.76 Ma.…”
Section: Evidence Of Biogeographical Barriers Driving Divergence Durimentioning
confidence: 96%